2023
DOI: 10.1186/s12974-023-02713-0
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis leads to central nervous system-wide glial activation in a mouse model of endometriosis

Abstract: Background Chronic pelvic pain (CPP) is a common symptom of endometriosis. Women with endometriosis are also at a high risk of suffering from anxiety, depression, and other psychological disorders. Recent studies indicate that endometriosis can affect the central nervous system (CNS). Changes in the functional activity of neurons, functional magnetic resonance imaging signals, and gene expression have been reported in the brains of rat and mouse models of endometriosis. The majority of the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 100 publications
0
5
0
Order By: Relevance
“…Researchers found that microglial cells in various regions of the brain were enlarged in a mouse model of endometriosis, indicating overall activation of these cells. This finding may have implications for understanding chronic pain and other neurological symptoms associated with endometriosis [ 218 ]. As the potential favorable effects of vitamin D in the context of neurological disorders [ 219 , 220 ], investigating the role of vitamin D in relieving neurologic complications related to endometriosis would be an active research area.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers found that microglial cells in various regions of the brain were enlarged in a mouse model of endometriosis, indicating overall activation of these cells. This finding may have implications for understanding chronic pain and other neurological symptoms associated with endometriosis [ 218 ]. As the potential favorable effects of vitamin D in the context of neurological disorders [ 219 , 220 ], investigating the role of vitamin D in relieving neurologic complications related to endometriosis would be an active research area.…”
Section: Discussionmentioning
confidence: 99%
“…It will be interesting to see how digging behaviors are affected by other models of visceral conditions associated with pain. Bashir and colleagues [4] have recently shown that mice undergoing a model of endometriosis are slower to burrow, from a tube filled with food pellets, than sham animals, however, both groups successfully clear the burrow within 24-hours. Such findings align with our argument that the burrowing assay is more task driven than digging.…”
Section: Discussionmentioning
confidence: 99%
“…The hallmark chronicity of this condition is consistent with the finding, discussed throughout this review, 2 of the TNF generated by activated microglia keeping these cells activated. Moreover, much evidence exists for microglial activation in this condition – particularly in experimental models, where it is very widespread 117 . It is also discussed in patient research 118,119 .…”
Section: Chronic Neurogenic Pain As a Consequence Of Increased Cerebr...mentioning
confidence: 99%
“…Moreover, much evidence exists for microglial activation in this condition – particularly in experimental models, where it is very widespread. 117 It is also discussed in patient research. 118 , 119 Should microglial activation become accepted as a key phenomenon in human endometriosis pain, an interest in perispinal administration of anti‐TNF therapy, as for post‐stroke pain, 17 , 53 is likely to be compelling.…”
Section: Chronic Neurogenic Pain As a Consequence Of Increased Cerebr...mentioning
confidence: 99%